P005 The effect of alcohol on the motor control of the genioglossus muscle. (7th October 2021) - Avraam, J; Dawson, A; Nicholas, C; Kay, A; O'Donoghue, F; Trinder, J; Jordan, A
Abstract: Rationale: Alcohol is recognised to worsen snoring and obstructive sleep apnea (OSA). This effect is thought to be due to alcohol's depressant effect on upper airway dilator muscles such as the genioglossus, but how alcohol reduces genioglossus activity is unknown. The aim of this study was to investigate alcohol's effect on genioglossus single motor units (SMUs). Methods: Healthy individuals visited the lab on two days (Alcohol: breath alcohol concentration ~0.08% or Placebo). They were instrumented with a nasal mask, 4 intramuscular genioglossus SMU EMG wires and an ear oximeter. They were exposed to 8–12 hypoxia trials (45-60s of 10%O2 followed by one breath of 100%O2) while awake. The SMUs were sorted according to their firing patterns with respect to respiration and were quantified during baseline, hypoxia, hyperoxia and recovery. Results: The total number of SMUs recorded at baseline (68 and 67 respectively) and their distribution (ET: 29 vs 22, IP: 5 vs 10, IT: 8 vs 20 and TT: 26 vs 15 respectively) was similar between conditions. The discharge frequency did not differ between conditions (21Hz vs 22.4Hz, p>0.08). There was no difference between placebo and alcohol in the number (101 vs 88 respectively) and distribution (ET: 35 vs 32, IP: 22 vs 16, IT: 14 vs 22 and TT: 30 vs 17 respectively, p<0.05) of SMUs during hypoxia. Afterdischarge following hypoxia was also not different between conditions. Conclusion: Alcohol has little effect on genioglossus SMUs and afterdischarge. OSA following alcohol may be related to increased upper airway resistance/nasal congestion.